Unexpected Decarbonylation of Acylethynylpyrroles under the Action of Cyanomethyl Carbanion: A Robust Access to Ethynylpyrroles - Denis N. Tomilin; Lyubov N. Sobenina; Alexandra M. Belogolova; Alexander B. Trofimov; Igor A. Ushakov; Boris A. Trofimov (Molecules, 2023)
It has been found that the addition of CH2CN− anion to the carbonyl group of acylethynylpyrroles, generated from acetonitrile and t-BuOK, results in the formation of acetylenic alcohols, which undergo unexpectedly easy (room temperature) decomposition to ethynylpyrroles and cyanomethylphenylketones (retro-Favorsky reaction). This finding allows a robust synthesis of ethynylpyrroles in up to 95% yields to be developed. Since acylethynylpyrroles became available, the strategy thus found makes ethynylpyrroles more accessible than earlier. The quantum-chemical calculations (B2PLYP/6-311G**//B3LYP/6-311G**+C-PCM/acetonitrile) confirm the thermodynamic preference of the decomposition of the intermediate acetylenic alcohols to free ethynylpyrroles rather than their potassium derivatives.